Implementation of the Integration of the National Curriculum and the Pesantren Curriculum and Its Impact on Students’ Academic Achievement - Ach. Muqoddas; Fitriyani Kosasih; Muhammad Aditya Firdaus (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the implementation of curriculum integration between the national curriculum and the pesantren (Islamic boarding school) curriculum and its impact on students’ academic achievement at MDS Al-Ma’arif and MDS Roudlotul Ulum in Bangkalan, Indonesia. Employing a mixed methods approach with a sequential explanatory design, the research began with quantitative data collection through surveys and academic documentation, followed by qualitative exploration via in-depth interviews and participatory observation. Findings reveal that MDS Al-Ma’arif applies a shared integration model, blending national and religious content into thematic modules (e.g., mathematics–faraid inheritance law), while MDS Roudlotul Ulum adopts a threaded integration model, using Arabic as the instructional language for science and mathematics taught through Sharia economic principles. Regression analysis identified three key factors influencing successful integration: teacher competency (β = 0.67), training intensity (β = 0.53), and technological infrastructure (β = 0.48). A mean difference test showed a significant academic performance gap between the two schools (Al-Ma’arif: 82.4; Roudlotul Ulum: 78.9; p = 0.001), along with a 23–27% improvement in students’ critical literacy. The study concludes that varied integration models within a single pesantren ecosystem can enhance academic outcomes without compromising Islamic identity. The research introduces the Cyclic Integration Model (CIM) as a theoretical contribution and proposes strategic recommendations for teacher training, development of integrative operational guidelines, and digital platforms grounded in Islamic values and 21st-century competencies.